IoT Multi Sensors - Lavric, Alexandru; Anchidin, Liliana; Petrariu, Adrian I. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on state-of-the-art technologies, the latest findings and current challenges in IoT with emphasis on healthcare, transportation, antenna design and disease detection. The included papers cover numerous topics of interest that include:IoT communication protocols;LPWAN for IoT (Sigfox, LoRa, etc.);Antenna design for IoT applications;Large-scale, high-density IoT networks and architectures;IoT applications and multi-sensors for transportation and traffic control;IoT convergence for Smart Health;Machine-learning/deep-learning algorithms for sensing IoT;Machine-learning-based healthcare applications and disease detection using IoT architectures;Applications and examples of use.